200th Anniversary of Rafiel Eristavi - Jagodnishvili, Temur ("Intercultural Dialogues" Transactions, 2025)
November 2024 marked the 200th anniversary of the birth of the famous Georgian poet and public figure – Rafiel Eristavi.This anniversary was celebrated in the format of sessions of one of the sections of the scientific conference. In addition, at the G. Leonidze Museum of Literature on February 11, 2025 were held a photo exhibition and presentation of the book „Raphiel Eristavi 200“. This book, although contains a photographic chronicle of the poet's life, literary-critical writings reviewing and evaluating his work, but it cannot be distinguished by the abundance of authors, the depth and comprehensiveness of the presentation of the creative, social, and scientific work of the famous figure. In addition, the planned collection of conference proceedings has not yet been published. This is how they modestly celebrated the 200th anniversary of the birth of an outstanding figure, Rafiel Eristavi, who made a significant contribution to the creation of Georgian culture in the 19th century. Unlike the 21st century, the 19th century more accurately read the great content of his work and paid him due respect. But Raf. Eristavi truly deserves great gratitude, love, recognition and immortality not only for his amazingly rich and multifaceted heritage, but also for creating a visible image of love for the homeland, inseparability from it, finding a poetic answer to the question: what is the homeland and love for the homeland? In the 1970s-1980s not a single significant public, national initiative or project was implemented in Georgian reality without his leadership or active participation; This would include the creation of a society for the dissemination of literacy among Georgians, the creation of a Georgian theatre society, the creation of a public library, the creation of a commission to determine the text of „The Knight in the Panther's Skin“ and the unique publication of the poem, the creation of a Georgian museum and much more. Raf. Eristavi was a great statesman – an official and translator for special affairs of the Tush-Pshav-Khevsureti Regional Administration, an special Affairs Officer of the Governor-General of Kutaisi, a provincial prosecutor, a manager of Samegrelo affairs, and the head of the Zugdidi district. However, everywhere and always, he was first and foremost a great patriot. In parallel with his civil service, he was prolific in writing – publishing poems, writing short stories, and dramatic works; He collaborated in the Georgian and Russian press, published sharp journalistic pieces and articles, and stood vigilantly guarding national interests; He was engaged in a surprisingly diverse activity in the field of science. He was a continuer of the scientific interests of European orientalism – a lexicologist and lexicographer, published the most important bilingual and trilingual dictionaries, laid the foundation for the tradition of compiling industry terminological dictionaries in our country, as well as dialectological and explanatory dictionaries. Raf. Eristavi also worked fruitfully in the fields of Georgian ethnography and folklore. Using direct observation and descriptive methods, he studied the traditional life of Tush-Pshav-Khevsureti, Tusheti, Imereti, Samegrelo, Samurzakano and Svaneti. He recorded and collected oral texts and published them in the form of letters and scientific studies in print, in collections of scientific societies and in separate books. The materials he found and discovered have not lost their historical and scientific value to this day, being indisputable facts and sources for modern scientific research. Along with this amazingly versatile work, he was a desirable and respected person in Georgian society, a leader of gatherings that he adorned with his personality. Georgian society appreciated Raf. Eristavi tireless work accordingly, which was primarily reflected in the constant public attention and love shown for his life and work. No other Georgian figure of the 19th century enjoyed such universal love and recognition as Raf. Eristavi. This was especially evident on October 22, 1895, when was celebrated on his 70th birthday and 50th anniversary of his public activity, in which the entire Georgian nation participated and the anniversary was called a public holiday. This anniversary became a fact of awakening of culture and national consciousness of the Georgian people and laid the foundation for the tradition of celebrating anniversaries among us. The work analyzes the facts of Raf. Eristavi's multifaceted activities and presents their national significance.